Stabilization of CCDC102B by Loss of RACK1 Through the CMA Pathway Promotes Breast Cancer Metastasis via Activation of the NF-κB Pathway - Si, Jing; Guo, Rong; Xiu, Bingqiu; Chi, Weiru; Zhang, Qi; Hou, Jianjing; Su, Yonghui; Chen, Jiajian; Xue, Jingyan; Shao, Zhi-Ming; Wu, Jiong; Chi, Yayun (Frontiers in Oncology, 2022)
Background Breast cancer is one of the leading causes of cancer-related death among women, and the pathological status of axillary lymph nodes is an important predictor of prognosis. However, the mechanism involved in this early stage of metastasis remains largely unknown. Methods Microarray analysis was used to carry out differential genomics analyses between matched pairs of metastatic sentinel lymph node tissues and breast primary tumors. The CRISPR/Cas9 gene editing system was used for in vivo screening by transplanting a loss-of-function cell pool into immunocompromised mice. MAGeCK was used to analyze the screening results. Survival analysis was performed via the Kaplan–Meier method. Cell proliferation, wound healing, migration and invasion assays were performed to confirm the phenotype. A tail vein model and subcutaneous xenotransplanted tumor model were used for the in vivo study. The relationship between coiled-coil domain containing 102B (CCDC102B) and receptor for activated C kinase 1 (RACK1) was examined using coimmunoprecipitation, mass spectrometry, nuclear protein extraction and immunofluorescence assays. The primary biological functions and pathways related to CCDC102B were enriched by RNA sequencing. Results We identified CCDC102B through screening and found that it was significantly upregulated in metastatic lesions in lymph nodes compared to matched primary tumors. Increased expression of CCDC102B promoted breast cancer metastasis in vitro and in vivo. Additionally, high expression of CCDC102B was correlated with poor clinical outcomes in breast cancer patients. We further identified that CCDC102B was stabilized by the loss of RACK1, a protein negatively correlated with breast cancer metastasis. Mechanistically, we found that RACK1 promoted CCDC102B lysosomal degradation by mediating chaperone-mediated autophagy (CMA). The aggressive behavior of CCDC102B in breast cancer cells could be reversed by the expression of RACK1. Moreover, CCDC102B was correlated with the significant enrichment of NF-κB pathway components. Overexpressing CCDC102B led to less interaction between RACK1 and IKKa. Thus, CCDC102B positively regulates the NF‑κB pathway by interacting with RACK1. Conclusion Taken together, our findings uncover a novel role of CCDC102B in breast cancer metastasis. CCDC102B serves as a potential metastasis promoter by regulating the activation of the NF-κB pathway and can be degraded by RACK1 via CMA.